O papel do estado e o direito humano à moradia: estudo de caso sobre a Ocupação Bubas em Foz do Iguaçu-PR - Vargas, Ian Martin (2020)
The present work has as object of study the Occupation Bubas, located in the city of Foz do Iguaçu - PR and characterized as the largest urban occupation in the state of Paraná. This choice is presented for the purpose of verifying the role of the state and the promotion of the human right to housing in this spatiality, since through bibliographical research, documentary research and field research it became possible to understand the current conditions of occupation, which are shown precarious and in need of further attention. Thus, the research is divided into five chapters, presenting the reflections on the state and housing, the legal foundation of the right to housing, urban occupations, the research methodology with interviews with important subjects that has relevant history of performance in the place. The reading of the data that were obtained through a case study that included questionnaires made in the community in question, demonstrated a great disregard of the Public Power in relation to the Bubas Occupation, affecting the entire local population and its relationship with the capitalist system itself. Therefore, analyzing the particularities of this research, it is shown that it has great relevance in relation to the study of the proportion of better conditions for individuals in areas of social vulnerability, thus seeking to provide spatial comfort, better living conditions and achieve what the population yearns and longs, making them protagonists of the urban space itself.